Lexical Co-occurrence and Lexical Inheritance. Emotion Lexemes in German: A Lexicographic Case Study - Mel’chuk, Igor A.; Wanner, Leo (Lexikos, 1994)
In the present paper, we tackle the problem of the compact and efficient representation of restricted lexical co-occurrence information in the lexicon along semantic lines. The theoretical framework for this study is the Meaning Text Theory (MTT) and, more specifically, the lexicographic part of MIT — the Explanatory Combinatorial Dictionary (ECD), which contains for each lexeme (i) its semantic definition, (ii) a systematic description of its restricted lexical co-occurrence in terms of Lexical Functions (LF), and (iii) its Government Pattern. The data domain is the semantic field of emotion lexemes in German. In order to represent the restricted lexical co-occurrence (or collocations) of the lexemes in this field, we suggest the following procedure: 1. Construct approximate descriptions of their meaning, i.e. what we call the abridged lexicographic definitions. Formulated in terms of semantic features, these definitions are supposed to provide as much semantic information as necessary for establishing correlations between the semantic features of a lexeme and its collocates. 2. Specify their syntactic Government Patterns, which are needed for a clearer picture of their co-occurrence — syntactic as well as lexical. 3. Specify their restricted lexical co-occurrence with the verbs chosen. 4. Establish correlations between the values of LFs and the semantic features in the abridged definitions of the emotion lexemes. 5. Based on these correlations, extract recurrent values of LFs (and recurrent Government Patterns) from individual lexical entries and list them under what we call the generic lexeme of the semantic field under study — in this case, GEFÜHL ’emotion’. This leads on the one hand, to "compressed" lexical entries for emotion lexemes, and on the other hand, to the creation of a lexical entry of a new type: the "public" entry of a generic lexeme. Keywords: lexicography, lexicon, german emotion lexemes, lexical co-occurrence, collocations, meaning text theory, lexical functions, semantic features, semantico-lexical correlations, information extraction, inheritance, individual lexical subentry, public lexical subentry